Basic Education Aspirations and Access to Secondary Education - St. Lucia. Ministry of Education and Culture (My University, 1989)
This paper gives an overview of the educational system with special reference to secondary education.
Caribbean Consultation Meeting for the World Conference on Education for All, Kingston, Jamaica, 22-24 November, 1989.
Keywords: Secondary education